Quiet eye training: A means to implicit motor learning - Vine, S. J.; Moore, L. J.; Cooke, A.; Ring, C.; Wilson, M. R. (International Journal of Sport Psychology, 2013)
The aim of this study was to determine if Quiet Eye (QE)-training might act as a form of implicit motor learning; enabling trainees to maintain performance under pressure by limiting the accrual of explicit rules governing performance. Forty-five novice golfers performed 40 Baseline and 320 acquisition golf putts in one of three instruction groups (QE, Analogy, Explicit). Learning and resilience to pressure were assessed in a Retention-Pressure-Retention design (60 putts) during which mean radial error, QE, conscious processing and explicit rule accrual were measured. The QE-trained group outperformed the Analogy group in the Retention tests and both other groups in the Pressure test; underpinned by superior visual attentional control (longer QE periods). The QE-trained group and the Analogy group reported fewer explicit rules and less conscious processing than the explicit group. QE training therefore appears to offer advantages in terms of both resilience to pressure and expedited skill acquisition.